Association of Socio-economic Status on Mahatma Gandhi National Rural Employment Guarantee Act of Rural Women in Alwar District of Rajasthan - Gupta, Shivani; Henry, Chitra; Sharma, S.K. (Indian Journal of Extension Education, 2013)
Mahatma Gandhi National Rural Employment Guarantee Act (MNREGA) is an important wage employment  programme. MNREGAwas notified in September 2005 and was launched on 2 February 2006. MNREGAis designed asnd a safety net to reduce migration by rural poor household in the lean period through aone hundred days of guaranteed  unskilled manual labour provided, when demanded at minimum wage on works focused on water conservation, land  development and drought proofing. The present study was conducted in Alwar district of Rajasthan because Alwar district  has second highest women population in Rajasthan. Four panchayat samities namely, Reni, Rajgarh, Umren, Thanagazi  were selected for the study purpose based on higher number of women who had completed hundred days employment  under MNREGA in the year 2008-09. Total sample size was 160 consisting of 80 beneficiary and 80 non-beneficiary  respondents. The data were collected through personal interview method. Study revealed that there is significant  association between age and socio-economic status of respondents. Achievement motivation level and source of  information utilized by respondent's exerted significant effect in development of socio-economic status of respondents.
Keywords: MNREGA; guaranteed labour; minimum wage; achievement motivation; socio-economic